AP-based CW Synchronization Scheme in IEEE 802.11 WLANs - Lee, Jin-Lee; Kyung, Yeunwoong (Society of Visual Informatics, 2021)
In this paper, an optimal CW (Contention Window) synchronization scheme is proposed in IEEE 802.11 WLANs. IEEE 802.11 WLANs operates with DCF (Distributed Coordination Function) mode for the MAC (Medium Access Control). In DCF, CW becomes the minimum CW according to the success of data transmissions and increases exponentially due to the collisions. In this situation, the smaller value of the minimum CW can increase the collision probability because stations have higher opportunity to access the medium. On the other hand, the higher value of the minimum CW will delay the transmission, which can result in the network performance degradation. In IEEE 802.11, since the base minimum CW value is a fixed value depending on the hardware or standard, it is difficult to provide the optimal network performance that can be determined by the flexible CW value according to the number of active stations. In addition, the synchronization of optimal CW is required among mobile stations to adapt the network parameters. Especially for the newly joined stations such as moving or turning on stations, they need to adapt the minimum CW value to get the optimal network performance. The shorter the adaptation time is, the better the network performance can maintain. Therefore, in this paper, AP (Access Point) calculates the optimal CW and shares it with mobile stations using beacon and probe response messages for the fast CW synchronization. Extensive simulation results show that the proposed scheme outperforms the previous schemes in terms of the network throughput and adaptation time. Â